2015
DOI: 10.1038/leu.2015.244
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of decitabine and gemtuzumab ozogamicin in newly diagnosed and relapsed acute myeloid leukemia and high-risk myelodysplastic syndrome

Abstract: Background Decitabine may open the chromatin structure of leukemia cells making them accessible to the calicheamicin epitope of gemtuzumab ozogamicin (GO). Methods 110 patients (median age 70 years; range 27–89 years) were treated with decitabine and GO in a trial designed on model based futility to accommodate subject heterogeneity: Group 1: relapsed/refractory AML with complete remission duration (CRD) < 1 year (N=28, 25%); Group 2: relapsed/refractory AML with CRD ≥1 year (N=5, 5%); Group 3: untreated AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…Other agents that DNMT inhibitors have been combined with in clinical trials include lenalidomide, carboplatin, cisplatin, gemtuzumab ozogamicin, erythropoietin, filgrastim, romiplostim, bortezomib, arsenic trioxide, and sorafinib (Blum et al 2012;Sekeres et al 2012;Greenberg et al 2013;Ravandi et al 2013;Glasspool et al 2014;Navada et al 2014;Daver et al 2015). These trials have produced mixed results about whether the combinations are beneficial and require further investigation, although the trials investigating the sensitization of cancers to platinum compounds by pretreatment with hypomethylating drugs have been particularly promising (Matei et al 2012).…”
Section: Combination Therapy With Dna Hypomethylating Drugsmentioning
confidence: 99%
“…Other agents that DNMT inhibitors have been combined with in clinical trials include lenalidomide, carboplatin, cisplatin, gemtuzumab ozogamicin, erythropoietin, filgrastim, romiplostim, bortezomib, arsenic trioxide, and sorafinib (Blum et al 2012;Sekeres et al 2012;Greenberg et al 2013;Ravandi et al 2013;Glasspool et al 2014;Navada et al 2014;Daver et al 2015). These trials have produced mixed results about whether the combinations are beneficial and require further investigation, although the trials investigating the sensitization of cancers to platinum compounds by pretreatment with hypomethylating drugs have been particularly promising (Matei et al 2012).…”
Section: Combination Therapy With Dna Hypomethylating Drugsmentioning
confidence: 99%
“…These results suggest that an anti-CD33 antibody and 5-azacytidine may act in concert to promote tumor cell killing. Daver et al demonstrated that decitabine and gemtuzumab ozogamicin improved the response rate but not overall survival compared with historical outcomes in untreated AML 60 years (45). To further explore the hypothesis of combining a DNA-methyltransferase inhibitor with an anti-CD33 antibody the ongoing study includes a cohort combining SGN-CD33A with a DNA-methyltransferase inhibitor (azacytidine or decitabine) for elderly treatment naïve patients with AML.…”
Section: Strategies To Improve Frontline Therapy In Elderly Amlmentioning
confidence: 99%
“…In patients receiving decitabine monotherapy, the rate of CR and overall response (OR) has been reported to be 13–39 and 32–70%, respectively (Iastrebner et al 2010; Kantarjian et al 2007a, c; Lee et al 2011; Oki et al 2012; Steensma et al 2009). Decitabine in combination with a variety of agents, including histone deacetylase inhibitors, thalidomide, and conventional chemotherapeutics, has been developed to treat intermediate- and high-risk MDS and AML (Blum et al 2007; Daver et al 2016; Gao et al 2015; Garcia-Manero et al 2006; Geng et al 2016; Jiang et al 2015; Kirschbaum et al 2014; Li et al 2015; Song et al 2012; Yang et al 2005; Zhao et al 2015). Several studies showed that decitabine in combination with chemotherapy improved the outcomes in patients with relapsed/refractory AML or AML transformed from MDS (MDS/AML) (Leonard et al 2014; Li et al 2015; Scandura et al 2011; Song et al 2012).…”
Section: Introductionmentioning
confidence: 99%